Ketokohan Al-Marbawi: Analisis Perkembangan Pengajian Ilmu Hadis: The Prominence of al-Marbawi’s Scholarship: An Analysis on the Development of the Sciences of Hadith - Ab Razak, Mohd Solleh; Shamsudin, Roshimah Shamsudin (‘Abqari Journal, 2021)
The recognition as a scholar upon al-Marbawi, whom significantly contributed in the scholarly literatures that which became reference for Muslims within the Malay Archipelagos is undisputed. In spite of the accolades, al-Marbawi was not spared from criticism; in which his background and qualifications in the discipline of hadith were disputed. The arguement stemmed from al-Marbawi's beginnings in the quest for hadith knowledge which was deemed unclear and further aggravated by the void in the details concerning the credence of his teachers. This article therefore aims to study the development of al-Marbawi's pursuit in acquiring his studies from his childhood to adulthood. To achieve these objectives, qualitative research was employed by way of library research in addition to content analysis methods that were fully used in the process of data collection and analysis. The findings show that there are two phases of study al-Marbawi's study of hadith; the basic phase of study being while he was studying in Malaya under the tutelage of Tuan Husin Kedah while the later stage refers to studies in his adulthood which took place in egypt involving formal studies at the al-Azhar University as well as informally through the books of Sahih Muslim and Jami‘ al-Tirmidhi. In summary, the varying periods of study of al-Marbawi proves that he was an authoritative scholar in the discipline of hadith.